Stress prevention through work reorganization : a summary of 19 international case studies. - KARASEK, Robert (1992)
Locates the cases in terms of the characteristics of the occupations selected for the prevention programmes. Reviews the types of stress problems identified for the programmes to resolve. Highlights the importance of this group of case studies in terms of the broad range of prevention methodologies spanned - with a concentration on workplace changes at several levels.